2018
DOI: 10.1159/000489089
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Topical 0.2% Sirolimus for Angiofibromas in Adults and Pediatric Patients with Tuberous Sclerosis Complex

Abstract: Background: Recent reports have suggested that the topical formulation of sirolimus is effective in treating facial angiofibromas in tuberous sclerosis complex (TSC). Here, we determined the safety and efficacy of 0.2% topical sirolimus for the treatment of facial angiofibroma and compared its effects based on age. Method: This was a retrospective study which involved 36 TSC patients with facial angiofibromas who were treated with 0.2% sirolimus ointment. Its effect was evaluated using the Facial Angiofibroma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…Lee et al investigated the efficacy of sirolimus ointment in 36 patients with AF, including three patients treated for over 1 year. The authors observed no further dramatic improvement after 20 weeks of treatment (14). Although the efficacy of sirolimus gel for AF is greater than that for topical sirolimus using other vehicles (8,11), sirolimus gel may exhibit limited efficacy for enlarged AF, similar to everolimus, which cannot diminish SEGA completely.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Lee et al investigated the efficacy of sirolimus ointment in 36 patients with AF, including three patients treated for over 1 year. The authors observed no further dramatic improvement after 20 weeks of treatment (14). Although the efficacy of sirolimus gel for AF is greater than that for topical sirolimus using other vehicles (8,11), sirolimus gel may exhibit limited efficacy for enlarged AF, similar to everolimus, which cannot diminish SEGA completely.…”
Section: Discussionmentioning
confidence: 92%
“…Although some previous studies have investigated the efficacy of topical sirolimus for AF among patients with TSC (7,8,(10)(11)(12)(13)(14)(15)(16), the follow-up period was only 6 months in most of these trials. Thus, the efficacy of long-term sirolimus gel treatment remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…thinner and more permeable. 9 With regard to ointment with tablets crushed in petrolatum, the presence of solid fragments may be responsible for the risk of bleeding and an uncomfortable sensation of oily skin has been observed. Recently, Bouguéon et al proposed a cream with 0.1% rapamycin solubilised with 5% Transcutol to avoid any bleeding problem and this oily sensation, with stability data.…”
Section: Introductionmentioning
confidence: 99%